Innovation, Real Primary Commodity Prices and Business Cycles - Bloch, Harry; Sapsford, D. (Springer-Verlag Berlin Heidelberg, 2013)
Schumpeter emphasizes the role of innovation in explaining long-run economic development. This contrasts to the emphasis on scarcity in classical and neoclassical models. Our research shows the fruitfulness of Schumpeter’s approach in explaining movements in real prices of primary commodities since 1650. In models that emphasize resource scarcity, rising real prices of these products are identified as limiting growth. However, in examining the historical data we find a dominance of negative price trends across individual commodities, particularly when allowing for long-run cyclical behavior. We then provide examples to show how innovations for particular commodities have contributed to the negative price trends. Overall, innovation has meant that increased supplies of primary commodities have been available at reduced real prices, thereby providing a positive contribution to growth. Of course, as Schumpeter suggests, the development process associated with innovation is uneven, so price movements are heterogeneous across long-run cycles and commodities.